2000
DOI: 10.1097/00004836-200007000-00006
|View full text |Cite
|
Sign up to set email alerts
|

What Predictive Parameters Best Indicate the Need for Emergent Gastrointestinal Endoscopy After Foreign Body Ingestion?

Abstract: Our aim was to determine what parameters may be used to indicate an emergent endoscopy after foreign body (FB) ingestion and to ascertain how often FBs are found endoscopically. Demographic data, gastroesophageal antecedents, clinical and endoscopic data, and complications were obtained. We examined 122 patients endoscopically. The onset of symptoms was immediate after FB ingestion in 93% of patients. Dysphagia was the most frequent symptom (66%), with the pharynx the most frequent location of impaction (71%).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
32
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 13 publications
1
32
0
2
Order By: Relevance
“…This figure is comparable with some eastern 4,10 and western 5,7,11 reported series, and differs from other reports 12,13 where endoscopy revealed the foreign body in only 52% and 64.5% of the patients. There are numerous reasons for this inconsistency, such as: the nature of the most common foreign bodies and food boluses, because the rate of spontaneous passage is related to the size and type of foreign body and food bolus; the incidence of the underlying esophageal disorders inducing stenosis, which obviously prevents spontaneous passage of the foreign body and food bolus; and finally the timing of the endoscopic procedure, because the chance of the foreign body passage through the GI tract spontaneously increases as time passes.…”
Section: Discussionsupporting
confidence: 81%
“…This figure is comparable with some eastern 4,10 and western 5,7,11 reported series, and differs from other reports 12,13 where endoscopy revealed the foreign body in only 52% and 64.5% of the patients. There are numerous reasons for this inconsistency, such as: the nature of the most common foreign bodies and food boluses, because the rate of spontaneous passage is related to the size and type of foreign body and food bolus; the incidence of the underlying esophageal disorders inducing stenosis, which obviously prevents spontaneous passage of the foreign body and food bolus; and finally the timing of the endoscopic procedure, because the chance of the foreign body passage through the GI tract spontaneously increases as time passes.…”
Section: Discussionsupporting
confidence: 81%
“…Pocos estudios previos han evaluado los factores clínicos que predicen la retirada del cuerpo extraño ingerido. Ciriza et al hallaron que la aparición inmediata de los síntomas, la presencia de disfagia y la ausencia de localización faríngea de la obstrucción constituían variables independientes que predecían un cuerpo extraño en la endoscopia gastrointestinal superior 7 . Lim et al hallaron que las pruebas de disfagia, frotis laríngeo positivo y de ingesta de agua eran de alta sensibilidad y especificidad en cuanto a la ingestión de cuerpos extraños 6 .…”
Section: Discussionunclassified
“…A previous study demonstrated that the immediate onset of symptoms, dysphagia, and the absence of pharynx localization of impaction were predictive of a positive FB finding. 17 Pharyngeal innervation by the vagus and glossopharyngeal nerves provides a better sensation than in the esophagus, which is innervated less densely by the vagus and cervical sympathetic nerves. 18 By contrast, our results demonstrate that dysphagia is an important positive predictor for real existing esophageal FBs while the lumping sensation over throat and odynophagia are not.…”
Section: Discussionmentioning
confidence: 99%